Optimasi Kinerja Sensor Value untuk Meminimalisir Kelembapan Udara Sebagai Pengganti Sinar Matahari - Sugiono sugiono; Unung Lesmanah; Arief Budi Laksono (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
Optimization of sensor value work on air humidity to generate renewable energy so that a Sensor Value is needed as a substitute for sunlight in the rainy season. In previous studies, there are several problems such as low sunlight in the resulting rainy season and the operation requires a long time, so one solution to overcome the above problems requires a Value sensor at a temperature of 800 C. In this research, there are two main objectives, namely increasing the efficiency of the system and simplifying the operation method. Increasing efficiency is done with several alternatives, namely minimizing the humidity of the surrounding air so that it can improve the sensor's work, while simplifying the operation is done by adding a value sensor module to adjust the heat focus. In the first stage of mechanization of value rays in the piping system, the second is testing of the sensor to the humidity of the surrounding air. This research will focus on the function of each component such as the heating room temperature sensor, while the main target is to generate heat in the rainy season